Model-based MIN/MAX override control of centrifugal compressor systems - Rico Schulze; Hendrik Richter (Franklin Open, 2024)
We propose an application-oriented nonlinear control approach for centrifugal compressors, tailored to meet requirements of industrial applications such as variable process demands and adherence to operational constraints, for instance surge avoidance. Our compressor model modifies an approach of Gravdahl and Egeland by including key features of an industrial setting. In particular, it takes into account the joint action of adjustable positions of the guide vane and the blow-off valve, while compensating variable disturbances introduced by the process valve. Moreover, the modified model is also valid for higher differential pressures across the compressor. By integrating the nonlinear output regulation framework with MIN/MAX-override control, we enable trajectory tracking within specified state constraints. Additionally, we analyze the switching scheme and give a proof of practical stability of the closed-loop MIMO system using the corresponding switched and impulsive error system. The effectiveness of the override control is demonstrated by typical scenarios in process control such as discharge pressure control, anti-surge control, and maximum discharge pressure limitation.